Applying the RAWEC Method for Material Selection of Crankshafts (International Journal of Scientific Research in Science and Technology, 2025)
The material used to manufacture crankshafts has a significant impact on the performance, durability, and lifespan of the product. While various materials can be employed for crankshaft production, selecting the optimal one from numerous available options is a complex task. This study aims to identify the most suitable material among four commonly used ones: 1080 steel, 18CrMo4 steel, 4130 steel, and S48C steel. Fifteen parameters were chosen to characterize each material, referred to as fifteen criteria. To rank the steel types, the RAWEC (Ranking of Alternatives with WEights of Criterion) method was employed. The results indicated that S48C steel is the most appropriate for crankshaft manufacturing.